Some Physical and Pasting Properties of Starch Isolated from Some Corn Genotypes Cultivated Under Sulaimani Governorate Condition - Maki Mohammed Ahmad Tarkhani; Muhammad Wajeeh M. Saeed Zainulabidden (University of Thi-Qar Journal of agricultural research, 2024)
This research was carried out on ten corn genotypes by cultivated all of genotypes in the year 2020 in Qlyasan research station location of College of Agriculture Engineering Science in Sulaimani University to produce seeds. The seeds were cleaned and ground to extract the starch from corn genotypes with purifications starch by Proteinase-K enzyme to purify the extracted starch from the residues protein that are still present in the starch. All corn genotypes’ physical and pasting characteristics has been studied in the lab, and statistically analyzed showed that there were substantial differences between all cornstarch genotypes. The physical properties included study these traits; starch granules distribution which maximum value recorded to medium as a percentage for all genotypes, maximum pH was 5.470, bulk density was 0.725 g/cm3, and maximum value of phosphate was 0.0235 %. Also, a study includes syneresis % which increase gradually in values for all genotypes by storage time, turbidity characteristic which decrease gradually for all corn starch genotypes with period of storage and the elements of pasting properties which includes; past temperature record 85 C˚, Peak Viscosity which was 584667 AU, peak temperature more than 95 C˚, cool paste viscosity (CPV) recorded 1220.000 AU and final element which was setback viscosity which record 735.00 AU.